Factors Affecting Students Performance - Transportation - Abd Majid, Muhammad Zulhakim (Journal of Computing Technologies and Creative Content, 2019)
A study was carried out to examine the perceptions and preferences of students on choosing the type of transportation for their travels in university campus. This study focused on for finding factors influencing student’s preferences. Overall a set of 16 question questionnaires were distributed to 100 students for conducted a research to investigate the choices of transportation mode preferences. Consequently, UNIKL MIIT and UKM students as respondents been used to identify the factors that affect the determination of the choice of transportation mode. Results indicated that preferences of using transportation among UNIKL MIIT students are mixed mostly due to accessibility. This study revealed positive aspects is needed for students to be able choose the best way possible to go the campus.